PENGARUH INDEKS PEMBANGUNAN MANUSIA , TINGKAT PENGANGGURAN DAN KEMISKINAN TERHADAP PERTUMBUHAN EKONOMI INDONESIA ( 2014-2023) - mayaguez, henky mayaguez; Kurniawan, Muhammad Kurniawan; Setyanto, Alief Rakhman (Salam (Islamic Economics Journal), 2024)
Development is something that is done to make things better in the future, according to the 1945 Constitution, the goal of Indonesia's national development is to create a more educated society and reduce violence, but this goal has not been fully achieved. One indicator that shows that the national development goals have not been achieved is the still high level of poverty in Indonesia. High levels of poverty will increase the costs of implementing development and will indirectly hamper development. The development process is not only related to growth but also increasing welfare, security, justice and the quality of natural resources and human resources. The development process, both in the economic and other fields, always involves human resources as the main foundation. The research was made with the aim of looking at the influence of the Human Development Index, Unemployment and Poverty on Indonesia's Economic Growth. The research method used is quantitative research by taking secondary data from BPS.